IDENTIFIKASI JENIS-JENIS IKAN PELAGIS KECIL YANG ADA DI PASAR IKAN SEGAR PASAR BENGKULU - Zulkhasyni; Silvy Syukhriani; Ayub Sugara; Ali Muqsit; Zerli Selvika; Firdha Iresta Wardani (University of Prof. Dr. Hazairin, SH, 2025)
Small pelagic fish are an important fish group with high economic value and play a key role in supporting fisheries production in Indonesia. However, data related to small pelagic fish remains limited, particularly in Bengkulu. One area with minimal documented fisheries data is Pasar Bengkulu. This study aims to identify the types of small pelagic fish found in the Pasar Bengkulu Fish Market. Data collection was carried out in June until Juli 2025 at Pasar Segar, Pasar Bengkulu. The method used in this study was descriptive exploration, which involved identifying the small pelagic fish sold in the Pasar Bengkulu Fresh Fish Market by analyzing and comparing their morphological characteristics based on fish identification references, including illustrations, photographs, and morphological descriptions. A total of eight fish species from eight genera and four families were recorded in the Pasar Bengkulu Fresh Fish Market. The most common small pelagic fish found was the weakfish, while the least common was kwee.